Long-term Potentiation at Temporoammonic Path-CA1 Synapses in Freely Moving Rats - Gonzalez, Jossina; Villarreal, Desiree M.; Morales, Isaiah S.; Derrick, Brian E. (Frontiers in Neural Circuits, 2016)
Hippocampal area CA1 receives direct entorhinal layer III input via the temporoammonic path (TAP) and recent studies implicate TAP-CA1 synapses are important for some aspects of hippocampal memory function. Nonetheless, as few studies have examined TAP-CA1 synaptic plasticity in vivo, the induction and longevity of TAP-CA1 long-term potentiation (LTP) has not been fully characterized. We analyzed CA1 responses following stimulation of the medial aspect of the angular bundle and investigated LTP at medial temporoammonic path (mTAP)-CA1 synapses in freely moving rats. We demonstrate monosynaptic mTAP-CA1 responses can be isolated in vivo as evidenced by observations of independent current sinks in the stratum lacunosum moleculare of both areas CA1 and CA3 following angular bundle stimulation. Contrasting prior indications that TAP input rarely elicits CA1 discharge, we observed mTAP-CA1 responses that appeared to contain putative population spikes in 40% of our behaving animals. Theta burst high frequency stimulation of mTAP afferents resulted in an input specific and NMDA receptor-dependent LTP of mTAP-CA1 responses in behaving animals. LTP of mTAP-CA1 responses decayed as a function of two exponential decay curves with time constants (τ) of 2.7 and 148 days to decay 63.2% of maximal LTP. In contrast, mTAP-CA1 population spike potentiation longevity demonstrated a τ of 9.6 days. To our knowledge, these studies provide the first description of mTAP-CA1 LTP longevity in vivo. These data indicate TAP input to area CA1 is a physiologically relevant afferent system that displays robust synaptic plasticity.